Solid-Phase Synthetic Strategies for the Preparation of Purine Derivatives - Krajčovičová, Soňa; Soural, Miroslav (ACS combinatorial science, 2016)
This Review summarizes all of the currently described strategies applicable for the solid-phase synthesis of purine derivatives. The individual approaches are classified according to the immobilization procedure used resulting in a linkage of the final scaffold at various positions.
Keywords: Combinatorial Chemistry Techniques; techniky kombinatorické chemie; purine; Purines; immobilization; combinatorial chemistry; techniky syntézy na pevné fázi; solid-phase synthesis; Solid-Phase Synthesis Techniques; indikátory a reagencie; xanthine; puriny; Indicators and Reagents